2021
DOI: 10.37496/rbz5020200207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wilting time and enzymatic-bacterial inoculant on the fermentative profile, aerobic stability, and nutritional value of BRS capiaçu grass silage

Abstract: The objective of this study was to evaluate the effects of wilting times and application of an enzymatic-bacterial inoculant on the fermentative profile and nutritional characteristics of BRS capiaçu grass silage in a semi-arid region. Four wilting times treatments (control, 6, 24, and 30 h), with or without the addition of an enzymatic-bacterial inoculant, were analyzed as a split-plot completely randomized design with eight replications. Parameters of the rumen degradability test were analyzed using a split-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
(40 reference statements)
1
14
0
4
Order By: Relevance
“…However, the use of additives can be an alternative to control the reduction in the dry matter content of mixed silages, since this mixture of forages results in gains in nutritional value of the ensiled material and that it is economically viable for the producer, allowing ensiling materials impossible to be ensiled in an exclusive way, guaranteeing additional feed roughage for critical times of the year, such as the dry season, for example. When it is not possible to use additives to increase the dry matter content of the mixed silage cotton to silk, pre-wilting elephant grass BRS capiaçu constitutes an auxiliary measure to be considered and can help in achieving suitable DM contents (Ribas et al, 2021). Thus, Oliveira et al (2017) analyzed elephant grass silages, with and without pre-wilting, and with and without inclusion of cassava meal, and demonstrated that pre-wilting increases silage DM.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of additives can be an alternative to control the reduction in the dry matter content of mixed silages, since this mixture of forages results in gains in nutritional value of the ensiled material and that it is economically viable for the producer, allowing ensiling materials impossible to be ensiled in an exclusive way, guaranteeing additional feed roughage for critical times of the year, such as the dry season, for example. When it is not possible to use additives to increase the dry matter content of the mixed silage cotton to silk, pre-wilting elephant grass BRS capiaçu constitutes an auxiliary measure to be considered and can help in achieving suitable DM contents (Ribas et al, 2021). Thus, Oliveira et al (2017) analyzed elephant grass silages, with and without pre-wilting, and with and without inclusion of cassava meal, and demonstrated that pre-wilting increases silage DM.…”
Section: Resultsmentioning
confidence: 99%
“…Kung, Shaver, Grant, & Schmidt, (2018) observed that DM content of grass silage should range from 25 to 35% for adequate fermentation, which highlights the importance of additives in increasing DM content. However, it is possible to observe adequate fermentation in BRS capiaçu grass with more than 20% DM (Jesus et al, 2021;Ribas et al, 2021).…”
Section: Aftermentioning
confidence: 99%
“…To facilitate its management, silage becomes a viable alternative, especially when using high potential forage for production of mass. Among the elephant grass cultivars, stands out the BRS capiaçu recently released by Embrapa (Pereira et al, 2017) with differential of high yield potential (72 tons dry matter -DM) and good nutritional value (crude protein of 94.2 g kg -1 DM and DM digestibility of 564 g kg -1 DM) as silage (Silva et al, 2019;Monção et al, , 2020aRibas et al, 2021). However, the dry matter content in the recommended maturity at harvest (90-120 regrowth days; 3.5-4.5 meters high) for ensiling is less than 20% (Pereira et al, 2017;Monção et al, 2019Monção et al, , 2020a, which may compromise the fermentation process in addition to presenting high effluent losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil has 167 million hectares of pasture, 80% of which belong to the genus Urochloa. However, the quantity and quality of forage throughout the year vary because of existing edaphoclimatic conditions, which affect the nutritional value of forage (Borges et al, 2019;Ribas et al, 2021). Dairy cows cannot express their genetic potential for milk yield under conditions of reduced nutritive value of the pasture, and supplementation with concentrate and/or roughage sources becomes necessary.…”
Section: Introductionmentioning
confidence: 99%